Crafting Entrepreneurship Behaviour among Youth to Preserve the Culture of Malaysian Handicrafts - Melissa W. MIGIN; Kishamala THAMOTHARAN; Hasliza HASSAN (Communications of International Proceedings, 2020)
Although handicrafts portray the Malaysian culture and heritage legacy brought forward from previous generations, over the years, due to industrial revolution and technological advancements, the handicraft industry has been severely affected. However, entrepreneurship is one of the ways forward to sustainably preserve the handicraft industry. Hence, using Azjen’s theory of planned behaviour (TPB), the aim of this research is to focus on the intention of the youth to venture into handicraft entrepreneurship as a path to rejuvenate the traditional handicrafts. The current study will extend the existing TPB framework by including the digital platform as an additional construct and will be based on cross-sectional quantitative findings. The target sample for this research comprises students from the National Craft Institute, Malaysia. This research aims to discover the entrepreneurial intention among the youth to pursue their careers in a traditional handicraft business. In line with the fourth industrial revolution, the impact of the digital platform will also be emphasized.
Keywords: Handicrafts; Malaysia; Entrepreneurial Intention; Digital Platform.